Penerapan Mesin Pencacah Sampah Berbasis IoT dan Energi Surya di Pulau Buluh: Teknologi Cerdas untuk Solusi Lingkungan yang Berkelanjutan - Lawi, Ansarullah; Dermawan, Aulia Agung; Candra, Joni Eka (Jurnal SOLMA, 2026)
Background: Buluh Island, one of Batam City’s coastal islands, faces a serious challenge in plastic waste management. Approximately two tons of waste are generated every four hours, but limited waste processing facilities result in most waste being burned or dumped into the sea, polluting the ecosystem and reducing fish catches. This threatens the economic sustainability of local communities, most of whom are fishermen. Method: This community service program provides a solution by implementing an Internet of Things (IoT)-based plastic shredder powered by solar panels. The technology is designed to operate independently from the conventional electricity grid and enables real-time monitoring via the Blynk application. The shredded plastic is then processed into economically valuable products such as paving blocks and handicrafts, supporting a circular economy. The community was actively involved in planning, installation, training, and machine maintenance, with the Buluh Island Waste Bank as the main partner. Results: The results show a reduction in plastic waste accumulation, increased community awareness of waste segregation, and key outcomes, including machine installation, training, media coverage, video documentation, and a draft journal publication. Conclusion: There is limited access to spare engine components and dependence on weather conditions for solar energy availability.